1994
DOI: 10.1002/pen.760340509
|View full text |Cite
|
Sign up to set email alerts
|

A property trend study of polybenzimidazole using molecular modeling

Abstract: Molecular mechanics and dynamics have become a standard analysis tool used in drug design and synthesis, but it has not generally been used as part of structural and mechanical analysis. The need for such tools is an obvious extension of structure‐property correlations known in polymer formulation, engineering, and manufacture. This study probes the use of mechanics and dynamics techniques to help explain property trends found in hydrated polybenzimidazole (PBI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…PBI loses its compressive strength at increased water content, which could be due to weakened van der Waals forces and hydrogen bonding interactions as a consequence of polymer swelling. Iwamoto et al [104] investigated the relationship between the tensile strength of PBI as a function of water content. They found that 10% water absorption resulted in a 25–30% decrease in the tensile strength.…”
Section: Pbi-based Composite Membranesmentioning
confidence: 99%
“…PBI loses its compressive strength at increased water content, which could be due to weakened van der Waals forces and hydrogen bonding interactions as a consequence of polymer swelling. Iwamoto et al [104] investigated the relationship between the tensile strength of PBI as a function of water content. They found that 10% water absorption resulted in a 25–30% decrease in the tensile strength.…”
Section: Pbi-based Composite Membranesmentioning
confidence: 99%
“…Although high water uptake improves proton conductivity, excessive absorbed water can deteriorate the membrane's mechanical strength, chemical stability, and dimensional stability due to the weakened hydrogen bonding interactions and Van der Waals forces caused by polymer swelling [35,87]. It has been reported that the tensile strength of the membrane decreases by about 25-30% with the addition of 10% water [88].…”
Section: Other Important Parametersmentioning
confidence: 99%
“…The water absorption of PBI is comparable to that of cotton (16%) and the absorbed water in PBI does not leave until the temperatures are well above 150 o . 2,4 Two possible molecular mechanisms are identified to be responsible for the high moisture absorption. The first is induced by two water molecules that are attached to each imidazole ring; the second is due to one water molecule that is attached to neighboring imidazole rings on adjacent polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…3 The absorbed moisture also influences the electrical insulation resistance and dielectric properties. 4 In addition, PBI can also be used as excellent thermal resistant coatings with a low friction surface for protection from mechanical abrasion, low coefficient of thermal expansion (similar to aluminum), high thermal and electrical insulation, and exceptional corrosion resistance to chemical attack in a wide range of substrate.…”
Section: Introductionmentioning
confidence: 99%